Avoidance expression in rats as a function of signal-shock interval: strain and sex differences - Servatius, Richard J.; Avcu, Pelin; Ko, Nora; Jiao, Xilu; Beck, Kevin D.; Minor, Thomas R.; Pang, Kevin C. (Frontiers in Behavioral Neuroscience, 2015)
Inbred Wistar Kyoto (WKY) rats express inhibited temperament, increased sensitivity to stress, and exaggerated expressions of avoidance. A long-standing observation for lever press escape/avoidance learning in rats is the duration of the warning signal (WS) determines whether avoidance is expressed over escape. Outbred female Sprague-Dawley (SD) rats trained with a 10-s WS efficiently escaped, but failed to exhibit avoidance; avoidance was exhibited to a high degree with WSs longer than 20-s. We examined this longstanding WS duration function and extended it to male SD and male and female WKY rats. A cross-over design with two WS durations (10 s or 60 s) was employed. Rats were trained (20 trials/session) in four phases: acquisition (10 sessions), extinction (10 sessions), re-acquisition (8 sessions) and re-extinction (8 sessions). Consistent with the literature, female and male SD rats failed to express avoidance to an appreciable degree with a 10-s WS. When these rats were switched to a 60-s WS, performance levels in the initial session of training resembled the peak performance of rats trained with a 60-s WS. Therefore, the avoidance relationship was acquired, but not expressed at 10-s WS. Further, poor avoidance at 10-s does not adversely affect expression at 60-s. Failure to express avoidance with a 10-s WS likely reflects contrasting reinforcement value of avoidance, not a reduction in the amount of time available to respond or competing responses. In contrast, WKY rats exhibited robust avoidance with a 10-s WS, which was most apparent in female WKY rats. Exaggerated expression of avoidances by WKY rats, especially female rats, further confirms this inbred strain as a model of anxiety vulnerability.